THE KNOWLEDGE MANAGEMENT IN BUSINESS STRATEGIES AND REVERSE LOGISTICS - Muniz Jr, Jorge [UNESP]; Cunha, Julio Cicero [UNESP]; Almeida, Reinaldo [UNESP]; Silva Marins, Fernando Augusto [UNESP] (Assoc Brasileira Engenharia Producao-abepro, 2017)
Environmental issues have changed the behavior of society and, consequently, the business environment. This has narrow approach with Knowledge Management techniques (KM) to promote their processes. However, despite the increase in research in this field, there is still lack of further study in the KM interface and the business environment, as suggested by several researchers. This work, in particular, seeks to identify the main gaps in the literature involving KM and Reverse Logistics (LR), and proposes relevant studies and hitherto insufficiently treated in the literature. For this 8.682 references were analyzed and these only 37 deal with such interface. So this paper proposes 6 topics to be researched.
Keywords: Knowledge Management; Reverse Logistics